2021
DOI: 10.1055/a-1701-2926
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Vaccine-Induced Immune Thrombotic Thrombocytopenia after ChAdOx1 nCoV-19 Vaccination and Safety of Second Vaccination with BNT162b2

Abstract: no abstract necessary because our manuscript is a letter to the editor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…10 Furthermore, a case study reported the high heterogeneity of clinical symptoms encountered during VITT. 11 The authors suggested that early detection and oral anticoagulation treatment might be beneficial for VITT patients. The unexpected but promising use of Bruton tyrosine kinase inhibitors should also be considered as an alternative to VITT treatment.…”
Section: Vaccine Complications and Anticoagulation In Covid-19 Patientsmentioning
confidence: 99%
“…10 Furthermore, a case study reported the high heterogeneity of clinical symptoms encountered during VITT. 11 The authors suggested that early detection and oral anticoagulation treatment might be beneficial for VITT patients. The unexpected but promising use of Bruton tyrosine kinase inhibitors should also be considered as an alternative to VITT treatment.…”
Section: Vaccine Complications and Anticoagulation In Covid-19 Patientsmentioning
confidence: 99%
“…In adverse immune reactions against drugs, recurrence of symptoms during re-exposure of the suspected compound is often considered proof of causality. In this regard, the observation that 34 VITT patients of the German cohort and 40 VITT patients of the UK cohort received their second vaccination shot with mRNA vaccines without signs of thrombosis or decreasing platelet counts is relevant [34] , [35] , [36] . This observation is strong in vivo evidence that the mRNA vaccines do not contain or induce cofactor(s) required for anti-PF4 antibody-mediated prothrombotic activation of platelets; especially as in the German cohort, several patients still had circulating platelet-activating anti-PF4 antibodies in their plasma at the time of the second shot mRNA vaccination.…”
Section: Pf4 As a Label Of Pathogensmentioning
confidence: 99%
“…In dieser Hinsicht sind klinische Beobachtungen an VITT-Patienten von Bedeutung, die jeweils eine 2. Impfung mit einem mRNA-Vakzin erhielten und in keinem Fall ein VITT-Rezidiv mit Thrombosen oder einer Thrombozytopenie entwickelten 49 50 51 . Dies unterstützt auch, dass mRNA-Vakzine keine Ko-Faktoren enthalten oder induzieren, die für eine Anti-PF4-Antikörper vermittelte prothrombotische Plättchenaktivierung notwendig wären.…”
Section: Die Pathogenese Der Vittunclassified